Tryptophan Metabolic Pathways Are Altered in Obesity and Are Associated With Systemic Inflammation - Cussotto, Sofia; Delgado, Inês; Anesi, Andrea; Dexpert, Sandra; Aubert, Agnès; Beau, Cédric; Forestier, Damien; Ledaguenel, Patrick; Magne, Eric; Mattivi, Fulvio; Capuron, Lucile (Frontiers in Immunology, 2020)
Background: Obesity is a condition with a complex pathophysiology characterized by both chronic low-grade inflammation and changes in the gut microbial ecosystem. These alterations can affect the metabolism of tryptophan (TRP), an essential amino acid and precursor of serotonin (5-HT), kynurenine (KYN) and indoles. This study aimed to investigate alterations in KYN and microbiota-mediated indole routes of TRP metabolism in obese subjects relatively to non-obese controls and to determine their relationship with systemic inflammation. Methods: Eighty-five obese adults (avg. BMI=40.48) and forty-two non-obese control individuals (avg. BMI=24.03) were recruited. Plasma levels of TRP catabolites were assessed using Ultra High Performance Liquid Chromatography-ElectroSpray-Ionization-Tandem Mass Spectrometry. High-sensitive C-reactive protein (hsCRP) and high-sensitive interleukin 6 (hsIL-6) were measured in the serum as markers of systemic inflammation using enzyme-linked immunosorbent assay. Results: Both KYN and microbiota-mediated indole routes of TRP metabolism were altered in obese subjects, as reflected in higher KYN/TRP ratio and lower 5-HT and indoles levels, relatively to non-obese controls. HsIL-6 and hsCRP were increased in obesity and were overall associated with TRP metabolic pathways alterations. Conclusion: These results indicate for the first time that KYN and indole TRP metabolic pathways are concomitantly altered in obese subjects and highlight their respective associations with obesity-related systemic inflammation.